Process for producing triacyglycerols containing arachidonic and docosahexaenoic acids for use in infant formulations - Lai, Oi Ming; Lo, Seong Koon (2009)

(untitled)
A process for producing triacylglycerols containing arachidonic and docosahexaenoic acids is provided by which involves separately hydrolysing the arachidonic acid enriched triacylglycerols and fish oil containing docosahaenoic acid to produce a free fatty acid fraction and docosahexaenoyl monoaccylglycerol fraction respectively, and thereafter esterifying al or a part of the free fatty acid fraction with the docosahexaenolt monoacylglycerol fraction. Separation and removal methods are performed to obtained a purified triacylglycerol product containing arahidonic and docosahexaenoic acids.